(untitled) (Journal of Hama University, 2025)
The research aimed to identify the digital skills required for teachers to use the Syrian educational platform and their level of mastery of it. To achieve the research objective, the researcher prepared a questionnaire consisting of two sections: the first section included personal data, while the second section consisted of (40) items divided into three axes. The questionnaire was applied to a sample of (97) male and female teachers who gave lessons on the Syrian educational platforms. The research identified (40) digital skills required for teachers to use the Syrian educational platform. The results also showed that the level of teachers’ mastery of the digital skills required to use the Syrian educational platform was average. The results also showed that there was no statistically significant difference in the level of teachers’ mastery of the digital skills required to use the Syrian educational platform according to the variable of academic qualification and according to the variable of educational stage.